Mendisiplin Anak Menurut Prinsip Kristen - Ayang Emiyati (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2018)
Ayang Emiyati, Disciplining Children According to Christian Principles. This article describes the treatment of disciplining children in Christian principles. To explain about disciplining children in the Christian principle, the author do literature review which then arranged systematically according to the construction of the concept of the author builds. Discipline is essentially necessary in the education of the child, only disciplinary action requires a wisdom and a love. Violent treatments are not the only way of discipline and discipline is not violence. Some things to consider in implementing discipline are to give priority to love in discipline, to use advises as a way of educating children, praying to surrender children to God, and make a beating as the last way in disciplining children.  Ayang Emiyati, Mendisiplin Anak Menurut Prinsip Kristen. Artikel ini memaparkan tentang tindakan mendisiplin anak dalam prinsip Kristen. Untuk memaparkan tentang mendisiplin anak dalam prinsip Kristen, penulis melakukan kajian literatur yang kemudian disusun secara sistematis sesuai konstruksi konsep yang penulis bangun. Disiplin pada intinya diperlukan dalam pendidikan anak, hanya tindakan mendisiplin memerlukan suatu hikmat dan adanya kasih.  Tindakan kekerasan bukanlah jalan satu-satunya dalam mendisiplin dan disiplin bukanlah suatu kekerasan. Beberapa hal yang perlu diperhatikan dalam melaksanakan disiplin adalah mengutamakan kasih dalam mendisiplin, memakai nasihat sebagai jalan yang dalam mendisiplin anak, doakan dan serahkan anak tersebut pada Tuhan, dan jadikan pukulan sebagai jalan terakhir dalam mendisiplin.